The Importance of Keeping Promises and Their Priorities According to the Perspective of the Qur'an Surah An-Nahl Verse 91 - Mohamad Rizal Hafiz; Friska Dwiyanti; Anggi Putri Dwi Neno (Aslama: Journal of Islamic Studies, 2024)
A promise or an oath are two different things but both must be kept because there is a trust in both. The use of these terms is very different in meaning and position, especially in the Qur'an. Promises and oaths if broken have the potential to harm the promised party to the loss of trust in the perpetrator. Departing from this, it is important to know what promises and oaths are in the Qur'an and what the position is for violators of promises and oaths according to the views of the mufassir. In this paper, researchers focus on Ibn Kathir's perspective on the interpretation of Al-Qur'an Surah an-Nahl/16: 91 in his tafsir book entitled Lubaabut Tafsir Miin Ibni Katsiir. This study aims to find out about the Importance of Keeping Promises and Its Virtues According to the Perspective of the Qur'an Surah An-Nahl Verse 91. The literature sources used are books, e-books, journals, articles, and trusted websites. Literature sources are collected by using search engines, and through libraries. The literature sources are then analyzed and concluded, the results of the literature study are made in the form of a systematic narrative by quoting and referring to literature sources. The writing format is adjusted to scientific principles and applicable guidelines. The data sources taken come from primary data, namely the book of interpretation Lubaabut Tafsir Miin Ibni Katsiir and secondary data from the literature relevant to the above title. The method used in this research is thematic method with descriptive analysis approach.